The importance of species interactions in eco-evolutionary community dynamics under climate change - Anna Åkesson (Nature Portfolio, 2021)
Understanding the dynamics of species interactions can help predict community responses to climate change. A spatially explicit model finds that species interactions and competition mitigate the harmful impacts of climate change, and that temperature-dependent competition makes communities more variable and responsive to changing climates.